VALUASI EKONOMI EKOSISTEM MANGROVE DI KOTA MUKOMUKO, KABUPATEN MUKOMUKO, PROVINSI BENGKULU - Zamdial Ta’alidin; Dede Hartono; Yar Johan (EnviroScienteae, 2019)
The purpose of this study is to calculate the economic valuation of mangrove ecosystems, as well as their contribution to the community in Mukomuko City, Mukomuko Regency, Bengkulu Province. This research was conducted by survey methods and using primary and secondary data. Primary data collection is done by observation and interview methods. The research respondents were determined by purposive sampling. Data analysis with qualitative descriptive method. The method of economic valuation was applied to estimate Total Economic Valuation (TEV) based on the total direct use value, indirect use value, option value, and existence value. Mangrove ecosystem in Mukomuko City is found in 3 locations (Bandar Ratu Village, Ujung Padang Village, and Pasar Mukomuko Village) with a total area of ± 121.14 ha. The composition of mangrove vegetation found in Mukomuko City consists of 4 true mangrove species and 1 non-mangrove species. The calculation results show that the TEV of the mangrove ecosystem in Mukomuko City is Rp. 7,135,622,252.76 per year or Rp. 58,903,931.41 per ha per year. Total Economic Value of the mangrove ecosystem in Mukomuko City consists of the direct use value of Rp. 732,600,000,- or Rp. 6,047,548.29,- per year; the indirect use value of Rp. 2,445,468,722.76,- or Rp. 20,187,128.30 per hectare per year; option value Rp. 25,984,530,- per year; existence value Rp. 3,858,309,000,- per year or Rp. 31,850,000 per hectare per year; and bequest value Rp. 73,260,000,- or Rp. 604,754.83 per hectare. The biggest use-value is the existing value, which is 54.07%, while the direct value only 10.22%.